USING PAIR AND GROUP WORK TO ENHANCE STUDENTS’ COMMUNICATION SKILLS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article explores the effectiveness of pair and group work as instructional strategies for enhancing students’ communication skills in English as a Foreign Language (EFL) classrooms. The study aims to investigate how collaborative learning activities influence students’ speaking fluency, interaction, and confidence. A mixed-methods approach was employed, including classroom observations, speaking assessments, and student questionnaires.